Determination of rheological, melting and sensorial properties and volatile compounds of vegan ice cream produced with fresh and dried walnut milk - Bekiroglu, Hatice; Goktas, Hamza; Karaibrahim, Dila; Bozkurt, Fatih; Sagdic, Osman (ELSEVIER, 2022)
Demand for vegan foods increases day by day and plant-based milks are used in the production of dairy products like ice cream. So, in this study two type of walnut milk, dried and fresh, was used to produce ice cream. The use of walnut milk in ice cream production significantly affected the physicochemical properties of ice cream samples and the fat content increased due to the high fat content of walnut. Overrun level of ice cream samples positively affected by using walnut milk in production of ice cream. The use of walnut milk in ice cream production improved the rheological properties, although it decreased brightness value of ice cream samples. Llimonene was determined as the major volatile compounds in all ice cream samples and it was determined that the use of walnut milk created different volatile compounds. Finally, according to the sensory evaluation results, the ice cream samples produced using walnut milk were liked by the panelists and received similar scores compared to the control, and this study showed that walnut milk can be used in ice cream production.
Keywords: Ice cream; Vegan; Walnut milk; Fat content; Sensory evaluation; Volatile compounds; QUALITY; HYDROCOLLOIDS; YOGURT; FAT; Food Science & Technology